Dynamic mechanisms of summer Korean heat waves simulated in a long‐term unforced Community Climate System Model version 3 - Han‐Kyoung Kim; Byung‐Kwon Moon; Maeng‐Ki Kim; Minho Kwon (Atmospheric Science Letters, 2020)
Abstract We investigate the natural variability of summer Korean heat waves through a long‐term (500 year) unforced simulation using the Community Climate System Model version 3. A total of 82 extreme heat wave frequency (HWF) years are identified with positive barotropic geopotential height (GPH) anomalies over the Korean Peninsula. These anomalies represent the most important atmospheric pattern that causes Korean heat waves via adiabatic warming by anomalous subsidence. From a composite analysis of the extreme Korean HWF years, the silk road pattern (SRP) and central Pacific (CP) sea surface temperature (SST) anomalies are selected as the driving factors of extreme Korean heat waves. The positive SRP is a west–east upper‐level Rossby wave train from the North Atlantic to East Asia under which positive barotropic GPH anomalies develop over the Korean Peninsula, thereby producing extreme heat waves. Cold CP SST anomalies induce cyclonic circulation and enhance convection over the subtropical western North Pacific through wind–evaporation–SST feedback, thereby acting as a source of the Pacific–Japan teleconnection pattern. They also cause positive barotropic GPH anomalies over the Korean Peninsula and intensify surface warming.